Tawāzun as A Moderator of Halal Product Choice Among Gen Z - Syahrul Syawal; Syaparuddin Razak; ABD. Rasyid R. (Universitas Persada Indonesia YAI, 2026)
This study examines the moderating role of Tawāzun , an Islamic ethical balance principle, in strengthening Generation Z’s awareness in selecting halal-packaged products. Drawing on the Theory of Planned Behavior (TPB) and Social Identity Theory (SIT), this research analyzes how attitudes, subjective norms, and perceived behavioral control influence intention, and how intention subsequently affects halal awareness. A quantitative explanatory design was applied using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with data obtained from 180 Muslim Gen-Z respondents in South Sulawesi, Indonesia. The findings show that attitude, subjective norms, and perceived behavioral control significantly determine intention, while intention strongly predicts awareness in choosing halal-packaged products. Intention also mediates the indirect effects of all TPB antecedents on awareness, confirming its role as the psychological mechanism that transforms cognition into ethical awareness. Moreover, Tawāzun demonstrates a significant direct effect on awareness and a modest moderating influence on the links between perceived behavioral control and intention as well as between intention and awareness. These findings highlight that halal consumption among Gen-Z is shaped not only by rational evaluation, but also by religious-ethical values and identity-based commitments, offering strategic implications for halal education, policy, and marketing.